ANALISA KEKUATAN TARIK PADUAN ALUMINIUM DENGAN MAGNESIUM PADA DUDUKAN SHOCKBREAKERUKURAN 70 X 30 X 30 mm - Zamah Syari (Reaktom : Rekayasa Keteknikan dan Optimasi, 2018)
Aluminium is a Non-Ferrous metal that is widely used in casting process, aluminium in pure state has poor mechanical properties, so it is necessary to add other alloying elements to improve its mechanical properties. so it is necessary to do research usingeksperimental method on aluminium-magnesium. The purpose of the research is to know the stress and strain with tensile test on aluminium-magnesium alloy to be used as material on motorbike shockbreaker holder with addition magnesium 3%, 5% and 7%. Tensiletest results show the mecanical properties of aluminium with The addition of magnesium elementer. The stress values of alloy of Al-Mg 3%, AlMg 5% and Al-Mg 7% were 161,15 MPa, 142,04 MPa And 91, MPa and 91,28 MPa respectively. And value of strain on alloys Al-Mg 3%, Al-Mg 5% and 7% is 0,05, 0,03 and 0,02. The stress and strain values can be seen diffferently on each test, The stress and strain values will decrease.